Lighting guide 5 : lighting for education - Butcher, Ken (Society of Light and Lighting, 2011)
Learning, whether by discussion, interaction, practical application or formal lecture, requires sufficient light to enable the pupils to see the visible information presented around them. Whether in a primary school classroom or a professional lecture theatre, whether for young or old, the quality of light in the learning environment will directly affect our learning experience and indeed our motivation to learn. Lighting Guide LG5: Lighting for education offers guidance on the lighting of all educational spaces including lecture theatres, teaching rooms, conference rooms, special-purpose rooms (such as gymnasia, art rooms and dance studios), multi-purpose rooms etc. In addition to providing guidance on the lighting equipment and its positioning, LG5 considers other important factors such as the decoration and finishes of rooms, sightlines, positioning of lighting controls and access doors, all of which need to be taken into account from the earliest stages of the planning process.